REVITALISASI FASILITAS INFORMASI DAN PENINGKATAN EDUKASI WISATA DI GOA NGERONG - Abdul Khamid Nasimul Askhia; Khozinatul Fikriya Shoda; Mita Putri Laksono; Ana Jamilatun Nabila; Desi Eka Saputri; Dhavi Yoga Aditama; Moh. Wahono Dwi Cahyono; Habibatus Sholihah; Aisyatum Bella; Siti Qoiriyah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study describes the revitalization and development of educational tourism in Ngerong Cave through the ABCD Community Service Program (KKN) of IAINU Tuban. Using a descriptive qualitative approach, this study outlines Group 4's efforts to revitalize the lesser- known tourist destination. The revitalization focused on physical improvements and strengthening educational values, including the installation of historical boards, information boards about flora and fauna, and tree nameplates. This activity aimed to transform Ngerong Cave from a mere entertainment venue into a sustainable, interactive learning space. In addition, the KKN group held a coloring competition for children as part of the educational tourism promotion, which successfully fostered a love of the environment from an early age. This effort demonstrates effective collaboration between KKN students, Village-Owned Enterprises (BUMDes), the community, and schools in enhancing tourist appeal and strengthening the identity of Ngerong Cave as an educational, nature-based and cultural destination.